The effects of supplementation with blueberry, cyanidin-3-O-β-glucoside, yoghurt and its peptides on obesity and related comorbidities in a diet-induced obese mouse model. (May 2019) - Shi, Min; Mathai, Michael L.; Xu, Guoqin; McAinch, Andrew J.; Su, Xiao Q.
Graphical abstract: The effects of blueberry and fermented yoghurt and their bioactive components [Cyanidin-3-O-β-glucoside (C3G) and peptides with angiotensin converting enzyme inhibitory activity] on obesity and its related comorbidities in high-fat-high-carbohydrate-diet (HFHC) induced obese mice. All results in supplementation groups were compared with the HFHC control group. Highlights: Blueberry and yoghurt alone reduce systolic and diastolic blood pressure in mice. Combined blueberry and yoghurt supplementation reduces systolic blood pressure. Yoghurt reduces body weight and body fat, and improved glucose tolerance (ipGTT). Combined peptides and C3G reduces blood pressure, body fat and improves ipGTT. Abstract: It is widely acknowledged that type 2 diabetes mellitus (T2DM) is associated with obesity, insulin resistance and hypertension. Cyanidin-3-O-β-glucoside (C3G), an anthocyanin in blueberry, and peptides with angiotensin converting enzyme (ACE) inhibitory activity derived from yoghurt are potentially beneficial for numerous health conditions including improving insulin resistance and glucose intolerance. In this study, the synergistic/additive effects of combined supplementations with blueberry and yoghurt, and C3G and peptides were determined. Blueberry and yoghurt alone, and the combination of C3G and peptides significantly reduced both systolic and diastolic blood pressure in diet-induced obese mice. Yoghurt supplementation significantly reduced body weight, percentage body fat and improved intraperitoneal glucose tolerance. Furthermore, peptides and the combination of peptides and C3G resulted in a significant reduction of percentage body fat and improved intraperitoneal glucose tolerance. As widely available, safe and nutritious foods, blueberry and yoghurt showed therapeutic potential in the treatment of obesity, diabetes and hypertension.